Recent advances in research in the rumen bloat of ruminant animals fed high-concentrate diets - Wang, Yusu; Wang, Lizhi; Wang, Zhisheng; Xue, Bai; Peng, Quanhui; Hu, Rui; Yan, Tianhai (Frontiers in Veterinary Science, 2023)
Rumen bloat is the most common digestive disorder in fattening ruminants, which is responsible for around 2 - 3 % of deaths in the ruminants industry and is therefore considered to be a serious threat to ruminant farming. The root cause of rumen bloat caused by feeding high concentrate dies would be attributed to the production of a large amount of stable foam during the fattening period. The exact mechanism of rumen foam formation has yet to be investigated. Proteins, polysaccharides and carboxylates derived from feed, and synthesised by microbes during the rumen fermentation may act as foaming agents or stabilizers in the formation progress of rumen foam. Supplementation of condensed tannins and other additives can be an effective way to prevent feedlot bloat induced by feeding high concentrate diets.